Local scour around complex abutments. (2nd November 2021) - Mohammadpour, Reza; Ghani, Aminuddin Ab.; Sabzevari, Tooraj; Fared Murshed, Mohamad
ABSTRACT: Local scour around complex abutment and pier is the main reason for bridges to collapse. Although the complex abutment/pier has been used in most rivers, there is limited research in the literature about the flow pattern and local scour at complex abutment/pier. In this study, a series of experimental test was conducted to predict local scour at complex abutments and provided results were compared with complex piers. The trend of local scour at compound abutments and piers was similar and considerably sensitive to the foundation level (Z). The top of foundation stops development of scour depth for several hours which depends on the abutment/pier size (L), foundation size and its level (Lf and Z). The minimum scour depth was observed for 1.0 <  Z/L  < 1.5. A novel equation with high accuracy ( R 2  = 0.97 and RMSE = 0.06) was developed for prediction of local scour at compound abutment based on effective length. This research highlights that the bridge cost can be reduced with a suitable design for the foundation level.